Системное представление знаний в концепции фреймов - Смоляга, Марина Витальевна; Старикова, Г. Г. (НТУ "ХПИ", 2015)
В статье рассматривается проблема структуры человеческих знаний. В частности, анализируется концепция представления человеческих знаний с помощью теории фреймов, разработанной М. Минским. Рассматривается структура фрейма как сложной иерархической системы. Анализируются различные типы систем фреймов, а также их подсистемы и суперфреймы. Обсуждаются возможности использования данных систем представления знаний для разработки искусственного интеллекта.

The article is devoted to the problem of human’s knowledge, for example, the unconscious, nonformalethated knowledge. The conception of the "third world of knowledge", created by K. Popper is analyzed as well as some conceptions about unconscious, nonverbal knowledge created by V. Nalimov, U. Varela, F. Maturana, N. Motroshilova, H. Knyazeva, H. Mikeshina and others philosophy. This aim is received by analyze the conception of representing human’s knowledge by the theory of framework which was made by M. Minsky. The structure of framework as a complexity system was investigated. The different types of frameworks systems also there small systems and superframes were analyzed. The possibilities of using such systems of human’s knowledge representing for elaborating the artificial intellect was discussed.
System representation of knowledge in the concept of frames
Keywords: представление знаний; реальность; фрейм; терминал; задания отсутствия; маркер; семантический фрейм; фрейм-сценарий; human’s knowledge representing; reality; framework; terminal; task of absence; marker; semantic framework; scenery-framework